Rancang Bangun Kwh Meter Digital 3 Phase Berbasis Microcontroller Melalui Sms Gateway Di Bandara Mopah Merauke - Mulyono, Subur (Fakultas Teknik dan Ilmu Komputer, 2023)
Mopah International Airport is an international airport located in the Merauke district, Merauke Regency, South Papua Province, Indonesia. Mopah International Airport was built in 1943 specifically for war emergency purposes. Currently this airport serves flights to Jayapura, Timika, Makassar, Surabaya and Jakarta. With a runway length of 2,250 m, it can be landed by Boeing 737 series aircraft. This study dealt by using the Design Of 3 Phase Digital Kwh Meter Based on Microcontroller through Sms Gateway. The aim of this study is to design a tool that can be used to monitor the consumption of electric power used. The method used in this research was observation, literature review, design method, and laboratory experiments. The results of this study are a mock-up that can be used to self-monitor the amount of electric power consumption that is used automatically connected to SMS. Keywords: 3 phase digital kwh meter, mickrocontroler, Sms gateway